APPLICATION OF THE LAW ON THE CRIME OF MONEY LAUNDERING AGAINST PERPETRATORS OF CRIME OBTAINED FROM THE PROCEEDS OF CORRUPTION - Mhd Azhali Siregar; Haris Putra Hutabarat; M. Fikri Akbar (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
The act of money laundering is very dangerous both at the national and international levels because money laundering is a means for criminals to legalize the proceeds of crime in order to eliminate traces. In addition, the nominal amount of money laundered is usually extraordinary, so it can affect national and even global financial balance sheets. The nature of the research used is normative legal research and the data collection method used in this research is secondary data obtained through library research, namely by conducting research on various literatures such as books, laws, which aim to find conceptions, or understandings related to the problem of applying the law of money laundering against criminals obtained from corruption. The crime of corruption is one part of special criminal law in addition to having certain specifications that are different from general criminal law, such as the existence of procedural law deviations and when viewed from the material regulated, the crime of corruption is directly or indirectly intended to minimize leakage and irregularities in the state's finances and economy. The application of the law on money laundering to the eradication of corruption aims to find out how to put the results of evidence on the case being examined, by what means the evidence is used and by what means the judge must form his belief before the court. In essence, in order to apply evidence or the law of evidence, the judge then starts from the evidentiary system with the aim of knowing how to put an evidentiary result on the case being tried.